Systemic blood pressure response to the inhibition of two hyperpolarizing pathways: a comparison to NO-synthase inhibition - Gerová, M; Kittová, M (Physiological research, 2006)
The impact on blood pressure of two vasodilating mechanisms, underlied by vascular smooth muscle hyperpolarization, was studied and compared to that induced by nitric oxide NO mechanism. Systemic blood pressure, after inhibitory intervention in arachidonic acid metabolism cytochrome P-450 inhibition by miconazole 0.5 mg/100 g b.w. , one of the hyperpolarizing pathways, did not change. After the inhibition of the action voltage-dependent K(+) channels operator by 4-aminopyridine 0.1 mg/100 g b.w. , the other hyperpolarizing pathway, blood pressure declined slightly from 132.3+/-3.2 mm Hg to 116.5+/-5.0 mm Hg, P<0.05 . Inhibition of nitric oxide production L-NAME 5 mg/100 g b.w. increased blood pressure considerably 123.5+/-2.7 mm Hg to 155.4+/-3.1 mm Hg, P<0.001 . After inhibition of the hyperpolarizing pathway by miconazole, hypotension induced by acetylcholine (Ach, 10 microg represented 63.0+/-1.9 mm Hg vs control value 78.6+/-5.2 mm Hg P<0.001 , by bradykinin (BK) 100 microg 59.4+/-3.9 mm Hg vs control value 71.2+/-6.1 mm Hg P<0.05 . After inhibition of the hyperpolarizing pathway by 4-aminopyridine, hypotension induced by ACh 10 microg achieved 64.6+/-2.5 mm Hg vs control value 78.4+/-2.8 mm Hg P<0.001 and that induced by BK 100 microg 56.6+/-5.3 mm Hg vs control value 72.3+/-2.5 mm Hg P<0.001 . ACh or BK hypotension after the inhibition of the above hyperpolarizing pathways was significantly attenuated. On the contrary, after NO-synthase inhibition the hypotension to ACh was significantly enhanced. Blood pressure decrease after ACh 10 microg hypotension was 91.8+/-4.1 mm Hg vs control value 79.3+/-3.3 mm Hg P<0.01 , and after BK 100 microg it was 78.4+/-7.1 mm Hg vs control value 68.3+/-5.2 mm Hg. A different basal BP response, but equally attenuated hypotension to Ach and BK, was detected after the inhibition of two selected hyperpolarizing pathways. In cotrast, the inhibition of NO production elicited an increase in systemic BP and augmentation of ACh and BK hypotension. The effectiveness of further hyperpolarizing mechanisms in relation to systemic BP regulation and nitric oxide level remains open.
Keywords: bradykinin; Dose-Response Relationship, Drug; Nitric Oxide Synthase; Rats; biologické faktory; vztah mezi dávkou a účinkem léčiva; systém (enzymů) cytochromů P-450; Potassium Channels, Voltage-Gated; Acetylcholine; inhibitory cytochromu P450; krevní tlak; Bradykinin; NG-nitroargininmethylester; Arachidonic Acid; acetylcholin; Miconazole; Rats, Wistar; mužské pohlaví; mikonazol; 4-aminopyridin; Potassium Channel Blockers; Cytochrome P-450 Enzyme System; krysa rodu Rattus; svaly hladké cévní; Muscle, Smooth, Vascular; arteriae carotides; Carotid Arteries; blokátory draslíkových kanálů; synthasa oxidu dusnatého; Cytochrome P-450 Enzyme Inhibitors; zvířata; Blood Pressure; draslíkové kanály řízené napětím; vazodilatancia; Biological Factors; Vasodilator Agents; kyselina arachidonová; potkani Wistar; 4-Aminopyridine; Enzyme Inhibitors; NG-Nitroarginine Methyl Ester; Male; inhibitory enzymů; Animals